Generating Virtual Environments to Allow Increased Access to the Built Environment - Foster, G. T.; Wenn, D. E. N.; Harwin, W. S.; O’Hart, F. (International Journal of Virtual Reality, 1998)
The problems encountered by individuals with disabilities when accessing large public buildings is described and a solution based on the generation of virtual models of the built environment is proposed. These models are superimposed on a control network infrastructure, currently utilised in intelligent building applications such as lighting, heating and access control. The use of control network architectures facilitates the creation of distributed models that closely mirror both the physical and control properties of the environment. The model of the environment is kept local to the installation which allows the virtual representation of a large building to be decomposed into an interconnecting series of smaller models. This paper describes two methods of interacting with the virtual model, firstly a two dimensional aural representation that can be used as the basis of a portable navigational device. Secondly an augmented reality called DAMOCLES that overlays additional information on a user’s normal field of view. The provision of virtual environments offers new possibilities in the man-machine interface so that intuitive access to network based services and control functions can be given to a user.